1994
DOI: 10.1002/em.2850230107
|View full text |Cite
|
Sign up to set email alerts
|

Detection of opiate‐enhanced increases in DNA damage, HPRT mutants, and the mutation frequency in human HUT‐78 cells

Abstract: In previous studies we have shown highly significant increases in chromosome damage and sister chromatid exchanges in heroin addicts, particularly when caffeine and metabolic inhibitors are added to the medium. Using human HUT-78 T-cell cultures, we now find direct in vitro evidence of opiate-induced or opiate-promoted mutagenesis via several assay systems. First, with microgel electrophoresis (MGE), we observed graded, dose-dependent, significant increases (P < .0001) in the frequency of comet tails of fragme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Chiesara et al found in peripheral lymphocyte DNA a 7.9 times greater incidence of chromosome anomalies in heroin‐marijuana addicts compared to marijuana‐only addicts. Opiates can indirectly increase the frequency of DNA damage and thereby amplify the occurrence of cells carrying mutagenic alterations . The second possible explanation may be related to immune suppression triggered by the opioids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chiesara et al found in peripheral lymphocyte DNA a 7.9 times greater incidence of chromosome anomalies in heroin‐marijuana addicts compared to marijuana‐only addicts. Opiates can indirectly increase the frequency of DNA damage and thereby amplify the occurrence of cells carrying mutagenic alterations . The second possible explanation may be related to immune suppression triggered by the opioids.…”
Section: Discussionmentioning
confidence: 99%
“…Opiates can indirectly increase the frequency of DNA damage and thereby amplify the occurrence of cells carrying mutagenic alterations. 31 The second possible explanation may be related to immune suppression triggered by the opioids. A forensic study of cadaveric thymus tissues showed that bleeding and dystrophic calcifications in the thymocyte's parenchyma were more common among intravenous drug abusers.…”
Section: Discussionmentioning
confidence: 99%
“…(24,25). Previously, various investigators reported that morphine enhances DNA damage in lymphocytic cells (37)(38)(39). These investigators suggest that opiates might be either decreasing the capacity to repair the damaged DNA or enhancing sensitization for DNA damage (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…Since the data from the chromosomal aberration effects in mouse lymphocytes has not been evaluated independently, it is not clear whether morphine is a unique in vivo positive, but this is worthy of further study. Increases in DNA fragmentation (Comet assay) and HPRT mutations have been reported in the human HUT-78 cell line exposed to morphine in vitro [36].…”
Section: Morphinementioning
confidence: 97%